Clinical profile, susceptibility patterns, speciation and follow up of infections by Elizabethkingia species: study on a rare nosocomial pathogen from an intensive care unit of north India. (November 2020) - Singh, S.; Sahu, C.; Singh Patel, S.; Singh, S.; Ghoshal, U.
Abstract: Elizabethkingia sp. is an opportunistic nosocomially acquired Gram-negative bacterium usually implicated in isolated cases of meningitis, pneumonia, bacteraemia and sepsis. It is a sturdy pathogen, resistant to most of the first-line antibiotics routinely used in laboratories for other Gram-negative pathogens. The current study was planned to assess the demographic profile, clinical picture, sensitivity patterns and species identification of various Elizabethkingia isolates, as well as to follow up cases of infection. All clinical samples of blood, cerebrospinal fluid and respiratory specimens positive for Elizabethkingia during a 2-year period were included in the study. The isolates were first identified with a Vitek-2 GN card system and further confirmed by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry. Follow-up visits of the patients with their demographic records, morbidities and treatment outcomes were also planned and studied. Over a period of 2 years, samples from 27 individuals showed positive growth of Elizabethkingia spp. Among these 27 individuals, 19 were adults and 8 were neonates. Blood samples yielded most isolates (52.6%; n  = 10); followed by tracheal aspirate, bronchoalveolar lavage fluid, and cerebrospinal fluid. Eleven out of 27 patients (40.7%) showed concomitant growth of other pathogens along with Elizabethkingia spp . ; predominantly Gram-negative organisms. Both species of Elizabethkingia showed 100% susceptibility to drugs such as minocycline and piperacillin-tazobactam . A favourable outcome was seen in 76.9% of the individuals with timely institution of antibiotics and proper diagnosis. Bloodstream infections and meningitis were identified as the most common clinical conditions associated with mortality. Infections due to Elizabethkingia are on the rise in developing countries like India. As a result there is an urgent need to study this pathogen in greater detail to understand its pathogenesis, clinical implications and treatment outcomes, especially in hospital settings such as intensive care units. Highlights: Elizabethkingia species is an opportunistic nosocomially acquired Gram negative bacteria usually implicated in isolated cases of meningitis, pneumonia, bacteremia, and sepsis. It is a sturdy pathogen resistant to most of the first line antibiotics routinely used in the laboratories for other Gram negative pathogens. It is implicated in a wide range of infections in both neonates and adults. Literature search reveals very scarce studies and case reports on this rare opportunistic pathogen in the healthcare settings and there is a dire need to study this pathogen in greater detail in a developing country like India.